Islamic ethical identity scorecard for Islamic markets; a comparison - Saw, Andrew Tek Wei (2018)
This study aims to continue the efforts of Adedokun (2015) in integrating Shariah screening methodology by using the Islamic Ethical Identity Scorecard. This study then applied the Islamic Ethical Identity Scorecard on Shariah compliance companies in Bangladesh and Pakistan. Results from both countries varied because of the different methodologies used in as well as the differences in reporting for annual reports in Bangladesh and Pakistan. Companies listed in the Chittagong Stock Exchange Shariah Index (CSI) of Bangladesh have higher quantitative compliances due to the fact that CSI used market capitalization in its methodology compared to the total asset base as used by the All Share Islamic Index of Pakistan. However, Pakistan scored better in qualitative screening due to the mandatory rule for public companies in Pakistan to showcase the payment of Zakat in their audited financial statements, which should be emulated in Bangladesh. It is hoped that this study would make a breakthrough in the process of unifying the previous models and improving Shariah screening standards. This would enable future researches to be developed based on this study’s formulated Islamic Ethical Identity Scorecard, which could be seen as a more wholesome and holistic approach to the Shariah screening methodology.